Inverse gas chromatography study of n-alcohols-poly(acrylonitrile-co-methylacrylate) systems - Coskun, M.; Ozdemir, E.; Celik, S.; Cansiz, A. (Publ by Marcel Dekker Inc, 1994)
Inverse gas chromatographic studies have been carried out on systems consisting of acrylonitrile (91.9%)-methylacrylate (8.9%) copolymer and ethanol, 1-propanol, 1-butanol, 1-pentanol, and 1-hexanol as probes. Molar heats (?Hs), free energies (?Gs) of sorption, Flory-Huggins ? parameters and weight fraction activity coefficients (a1/w1)?, were computed for these systems in the range 110-140 °C, above glass transition temperature of the copolymer. The solubility parameter of the copolymer at 25 °C was estimated from data in the temperature range of 110-140 °C. Molar heats of vaporization of n-alcohol probes (?Hv) were determined from gas chromatographic data and the results compared with those of calculated using critical temperatures, boiling temperatures, and molar heats of vaporization of the probes at boiling temperatures.
Keywords: Alcohols; Gas chromatography; Glass transition; Mathematical models; Mixtures; Parameter estimation; Polyacrylates; Polyacrylonitriles; Solubility; Sorption; Thermodynamic properties; Vaporization; Inverse gas chromatography; Poly(acrylonitrile-co-methylacrylate); Copolymers